Маєстат Франкового слова - Єрмоленко, С. (Культура слова, 2016)
Стаття присвячена аналізові поетичної мови І. Франка. Простежено шлях формування символічного значення слів із узагальненою абстрактною семантикою, наповнення висловів громадянського звучання філософським змістом, поєднання конкретно-чуттєвих образів української мови із логічно- поняттєвими структурами, що забезпечує інтелектуально- емоційну глибину Франкової поезії. The article is devoted to the analysis of I. Franko’s poetry language. The path of formation of the symbolic meaning of the words with generalized abstract semantics, the filling of the expressions of civic sound with the philosophical content, the combination of specific sensory images of the Ukrainian language with logical and conceptual structures, which provides the intellectual and emotional depth of Franko’s poetry, is traced.